Cognitive Bias Modification Training During Inpatient Alcohol Detoxification Reduces Early Relapse: A Randomized Controlled Trial. (4th August 2016) - Manning, Victoria; Staiger, Petra K.; Hall, Kate; Garfield, Joshua B.B.; Flaks, Gabriella; Leung, Daniel; Hughes, Laura K.; Lum, Jarrad A. G.; Lubman, Dan I.; Verdejo‐Garcia, Antonio
Abstract : Background: Relapse is common in alcohol‐dependent individuals and can be triggered by alcohol‐related cues in the environment. It has been suggested that these individuals develop cognitive biases, in which cues automatically capture attention and elicit an approach action tendency that promotes alcohol seeking. The study aim was to examine whether cognitive bias modification (CBM) training targeting approach bias could be delivered during residential alcohol detoxification and improve treatment outcomes. Methods: Using a 2‐group parallel‐block (ratio 1:1) randomized controlled trial with allocation concealed to the outcome assessor, 83 alcohol‐dependent inpatients received either 4 sessions of CBM training where participants were implicitly trained to make avoidance movements in response to pictures of alcoholic beverages and approach movements in response to pictures of nonalcoholic beverages, or 4 sessions of sham training (controls) delivered over 4 consecutive days during the 7‐day detoxification program. The primary outcome measure was continuous abstinence at 2 weeks postdischarge. Secondary outcomes included time to relapse, frequency and quantity of alcohol consumption, and craving. Outcomes were assessed in a telephonic follow‐up interview. Results: Seventy‐one (85%) participants were successfully followed up, of whom 61 completed all 4 training sessions. With an intention‐to‐treat approach, there was a trend for higher abstinence rates in the CBM group relative to controls (69 vs. 47%, p  =   0.07); however, a per‐protocol analysis revealed significantly higher abstinence rates among participants completing 4 sessions of CBM relative to controls (75 vs. 45%, p  =   0.02). Craving score, time to relapse, mean drinking days, and mean standard drinks per drinking day did not differ significantly between the groups. Conclusions: This is the first trial demonstrating the feasibility of CBM delivered during alcohol detoxification and supports earlier research suggesting it may be a useful, low‐cost adjunctive treatment to improve treatment outcomes for alcohol‐dependent patients. Abstract : In a RCT, 83 alcohol‐dependent patients received either cognitive bias modification (CBM) or sham training (controls), during inpatient withdrawal. Among the 86% followed up 2 weeks postdischarge, significantly higher rates of abstinence were reported among the CBM group relative to controls if they completed the intended protocol of four training sessions ( p  = 0.02). The findings demonstrate the feasibility of CBM delivered during alcohol detoxification and support earlier research suggesting it may be a useful, low‐cost adjunctive treatment to improve treatment outcomes.